Dlaczego warto łączyć nauczanie matematyki z ruchem i muzyką? Wybrane przykłady badań na temat łączenia różnych form w zintegrowanej edukacji wczesnoszkolnej = Why is it worth combining teaching mathematics with movement and music? Selected examples of research on combining different forms in integrated early childhood education - Łuczak, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with combining mathematical education with other forms of classes and contains a presentation of selected examples of research on combining mathematics teaching with music and movement. On the basis of the results of empirical studies the text presents the limitations of material integration in various fields, but above all, the advantages of this type of approach.
Keywords: matematyka; ruch; muzyka; edukacja wczesnoszkolna; kształcenie zintegrowane; mathematics; movement; music; early childhood education; integrated education